1999
DOI: 10.1074/jbc.274.32.22184
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Yeast Mitochondrial Transporter for Oxaloacetate and Sulfate

Abstract: Saccharomyces cerevisiae encodes 35 members of the mitochondrial carrier family, including the OAC protein. The transport specificities of some family members are known, but most are not. Saccharomyces cerevisiae has two principal pathways for replenishing the intermediates of the Krebs cycle that have been withdrawn for biosynthesis. They are the glyoxylate cycle and the carboxylation of pyruvate to oxaloacetate, catalyzed by two cytosolic isozymes of pyruvate carboxylase. (Mammalian pyruvate carboxylase is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
93
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 44 publications
1
93
0
Order By: Relevance
“…In yeast, the existence and importance of the malate-aspartate shuttle has been debatable until the transporters required for the malate-aspartate shuttle to operate were identified (Palmieri et al 1996(Palmieri et al , 1999(Palmieri et al , 2001Cavero et al 2003). Here our data showed that the malate-aspartate shuttle played a major role in mediating life span extension under CR as well as in Multiple CR pathways act to affect longevity in yeast.…”
Section: Discussionmentioning
confidence: 55%
“…In yeast, the existence and importance of the malate-aspartate shuttle has been debatable until the transporters required for the malate-aspartate shuttle to operate were identified (Palmieri et al 1996(Palmieri et al , 1999(Palmieri et al , 2001Cavero et al 2003). Here our data showed that the malate-aspartate shuttle played a major role in mediating life span extension under CR as well as in Multiple CR pathways act to affect longevity in yeast.…”
Section: Discussionmentioning
confidence: 55%
“…Oac1p transports oxalacetate into the yeast mitochondrial matrix with protons or by exchange with other substrates and operates with the same transport properties in vivo and in reconstituted liposomes (26). In the same study, it was suggested that the role of Oac1p is to take up into mitochondrial oxalacetate produced by pyruvate carboxylase, which in S. cerevisiae is only cytoplasmic.…”
Section: Discussionmentioning
confidence: 84%
“…In a previous study, Oac1p was shown to be the yeast mitochondrial transporter for oxalacetate and sulfate (26). Oac1p transports oxalacetate into the yeast mitochondrial matrix with protons or by exchange with other substrates and operates with the same transport properties in vivo and in reconstituted liposomes (26).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Yhm2p shares only 21 and 22% identical amino acids with Ctp1p and CTP, respectively. Yhm2p also differs from the dicarboxylate (38,39) and oxaloacetate (16,40) 1 from Plasmodium falciparum (31%) and XP_001238657.1 from Eimeria tenella (31%)), Euglenozoa (e.g. XP_811279.1 from Trypanosoma cruzi (32%)), and Stramenopiles (e.g.…”
Section: Discussionmentioning
confidence: 99%